Facile Synthesis of Binder-Free Three-Dimensional CuxS Nanoflowers for Lithium Batteries - Adylkhanova, Assyl; Nurpeissova, Arailym; Adair, Desmond; Bakenov, Zhumabay; Taniguchi, Izumi; Kalimuldina, Gulnur (Frontiers in Energy Research, 2020)
Copper sulfides (CuxS) with different stoichiometry are considered as prospective cathode materials for lithium batteries owing to their large energy storage capability. In this work, three-dimensional CuxS cathodes were synthesized via introducing commercially available copper foam into the solution of dimethyl sulfoxide (DMSO) and sulfur powder. The synthesis procedures were straightforward and ultrafast and did not require additional reagents, high temperature, or long processing time and can be considered as a facile one-step method. Copper sulfide materials with different stoichiometry (x = 1.8, 1.96) were obtained by changing the temperature and the residence time of the copper foam in the DMSO solution. The effects of the temperature and time on phase and morphology of CuxS were characterized by X-ray diffraction and scanning electron microscopy coupled with energy dispersive X-ray spectroscopy. Electrochemical tests resulted in a stable cyclability of Cu1.8S cathode with 100% Coulombic efficiency and capacity of approximately 250 mAh g–1.